Kehamilan Aman dan Nyaman dengan Pendampingan di Kelas Ibu Hamil Puskesmas Jenggot Kota Pekalongan - Hilda Prajayanti; Swasti Artanti; Putri Andanawarih (LPPM Akbid Harapan Ibu Pekalongan, 2023)
Pregnant Women's Class is a study group for pregnant women with gestational age between 4 weeks to 36 weeks (before delivery). Safe and comfortable pregnancy is one of the stages of life that must be prepared by a woman, in the process of pregnancy there are physiological and psychological changes due to an increase in estrogen and progesterone. Risk factors for maternal mortality during the delivery process begin with an unmonitored pregnancy. Efforts to reduce maternal mortality through maternity classes. This pregnant women class is a means to learn together about health for pregnant women, in the form of face-to-face in groups aimed at increasing the knowledge and skills of mothers regarding pregnancy, pregnancy care, childbirth, postpartum care, newborn care, myths, infectious diseases and birth certificates. The purpose of this community service is to increase the knowledge of pregnant women about pregnant women's classes. The method of providing material presented is (1) Newborn care for optimal growth and development and body mechanics, (2) safe delivery, safe postpartum, safe mother and healthy baby, (3) danger signs for pregnant women in Trimester III. Evaluation of the results of pregnant women's class activities with Post Test. The results of this activity can increase the knowledge and understanding of participants about the importance of pregnant women's classes so that they can maintain health during pregnancy and prevent / detect early if complications occur in pregnancy.